SOCIAL DISCLOSURE AND GOVERNANCE AMONG MALAYSIAN CORPORATIONS - Pei, Sze Ng; Asri, Marsidi (UNIMAS Publisher, 2022)
The objective of the study is to examine the relationship between corporate governance mechanisms and corporate social responsibilities (CSR) disclosure among Malaysian leading corporations on Bursa Malaysia. The research is carried out due to the relatively low awareness and inconsistency with respect to the CSR disclosure particularly in Malaysia. The study uses the annual reports and data stream to collect the data of 50 Malaysian top corporations on Bursa Malaysia in 2015. The multivariate analysis suggests that the audit committee expertise and the foreign shareholding have significant relationships with CSR disclosure in Malaysia. In this sense, having a clear understanding on the corporate governance characteristics is perceived as able to increase the disclosure of CSR information to the respected stakeholders. The study therefore contributes to the theories, literature and practice. In this perspective, the study highlights the importance of having a sound corporate governance structure in enhancing CSR information disclosure. In overall, the results of the study can be regarded as valuable to the corporate players, corporations, relevant statutory authorities as well as other related parties.